2013
DOI: 10.1152/ajpendo.00359.2012
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B-6 restriction impairs fatty acid synthesis in cultured human hepatoma (HepG2) cells

Abstract: Vitamin B-6 deficiency has been reported to alter n-6 and n-3 fatty acid profiles in plasma and tissue lipids; however, the mechanisms underlying such metabolic changes remain unclear. The objective of this study was to determine the effects of vitamin B-6 restriction on fatty acid profiles and fatty acid synthesis in HepG2 cells. Cells were cultured for 6 wk in media with four different vitamin B-6 concentrations (10, 20, 50, and 2,000 nM added pyridoxal, representing deficient, marginal, adequate, and suprap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…The Δ6 desaturase is a PLPdependent enzyme, required for the interconversion of highunsaturated fatty acids (HUFA) (18) into PUFA such as arachidonic acid (20 : 4 n-6) and DHA (22 : 6 n-3). This was also observed in one in vitro study with cultured cells (48) in which a reduction in vitamin B 6 levels led to changes in the n-3 and n-6 long-chain PUFA profile in parallel with reductions in the rate of the desaturation processes. They also found that concentrations of total FA and PL species were higher in vitamin B 6 -deficient cells, as it was also observed in some studies in rats (49,50) .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The Δ6 desaturase is a PLPdependent enzyme, required for the interconversion of highunsaturated fatty acids (HUFA) (18) into PUFA such as arachidonic acid (20 : 4 n-6) and DHA (22 : 6 n-3). This was also observed in one in vitro study with cultured cells (48) in which a reduction in vitamin B 6 levels led to changes in the n-3 and n-6 long-chain PUFA profile in parallel with reductions in the rate of the desaturation processes. They also found that concentrations of total FA and PL species were higher in vitamin B 6 -deficient cells, as it was also observed in some studies in rats (49,50) .…”
Section: Discussionsupporting
confidence: 63%
“…In view of the observed associations, this second pathway is less likely to explain our results, as more consistent associations were found for folate and vitamin B 12 biomarkers than for PLP (vitamin B 6 biomarker). However, it is suggested elsewhere (48) that this pathway is more probable than the first one as SAM concentrations were higher, but SAH was lower in the cultured cells with vitamin B 6 restriction. However, the study did not consider the interaction between folate and vitamin B 12 .…”
Section: Discussionmentioning
confidence: 83%
“…Low serum concentrations of vitamin B 6 are associated with lower estimated D5D and D6D activity indexes in healthy people [ 43 ], and vitamin B 6 -deficiency has shown to decrease the activity index of D6D in rat liver microsomes [ 44 ]. Moreover, high levels of vitamin B 6 have been reported to increase both D5D- and D6D mRNA levels in HepG2 cells [ 5 ]. These results may suggest that folate and vitamins B 6 and B 12 influence genes and enzymes involved in the metabolism of LCPUFA.…”
Section: Discussionmentioning
confidence: 99%
“…The study on volunteers with marginal nutritional deficiency of vitamin B6 showed decreased plasma concentrations of polyunsaturated fatty acids (PUFA) of the n−6 and n−3 families, whereas the levels of TC, LDL-C, HDL-C, and TAG did not change [ 43 ]. Altered synthesis of unsaturated, particularly n−6 and n−3 PUFA, was proved in cultured human hepatoma (HepG2) cells under the condition of vitamin B-6 restriction [ 44 ]. These changes could participate in mechanisms by which vitamin B-6 inadequacy influences cardiovascular risk [ 44 ].…”
Section: Niacin and Other B Vitamins In Cardiovascular Riskmentioning
confidence: 99%